2013
DOI: 10.1073/pnas.1308846110
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic origins of protein folding, allostery, and capsid formation in the human hepatitis B virus core protein

Abstract: Significance Hepatitis B virus (HBV) is a major pathogen, yet no fully effective therapies exist. HBc is the multifunctional, capsid-forming protein essential for HBV replication. HBc structural plasticity is reportedly functionally important. We analyzed the folding mechanism of HBc using a multidisciplinary approach, including microscale thermophoresis and ion mobility spectrometry–mass spectrometry. HBc folds in a 3-state transition with a dimeric, helical intermediate. We found evidence of a stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(93 citation statements)
references
References 63 publications
3
90
0
Order By: Relevance
“…Attractive hydrophobic interactions have been thought to guide specific interactions during the assembly of viral capsids (17). However, in this study, the surface-exposed negative charges on the spike tip greatly influenced the assembly efficiency of the HBc subunits (Fig.…”
Section: Hydrophobic Interaction and Electrostatic Repulsion During Hmentioning
confidence: 77%
“…Attractive hydrophobic interactions have been thought to guide specific interactions during the assembly of viral capsids (17). However, in this study, the surface-exposed negative charges on the spike tip greatly influenced the assembly efficiency of the HBc subunits (Fig.…”
Section: Hydrophobic Interaction and Electrostatic Repulsion During Hmentioning
confidence: 77%
“…[16][17][18][19][20][21][22][23], in the a2b helix, and the junction with the a3 helix (peptide [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55], and in the junction between a4b and a5 helices (peptide 104-116). Peptides were not identified for the central region of the a3 helix (residues [56][57][58][59][60][61][62][63][64][65][66][67][68] and the N-terminal half of the a5 helix (residues 121-125), hence the deuterium incorporation of these regions is unknown. Viewed in the context of the folded structure, the overall pattern of incorporation is clear [ Fig.…”
Section: Hdx-ms Of Cp149 Dmentioning
confidence: 99%
“…56 shown that the capsid dimer has points of inherent strain, giving it access to different conformations. 57 As the pathway of co-translational folding and association of the Cp149 chains in vivo is necessarily different from the dissociation and re-association of complete Cp(210)149 chains in vitro it is not implausible that the conformations of some parts of the two structures, such as the E1 epitope, could be subtly different.…”
Section: Binding Of Fab E1mentioning
confidence: 99%
See 1 more Smart Citation
“…These estimates, while broadly consistent with the values obtained from sequence-based secondary structure predictions for RT-RH 303-778 (ϳ29% ␣-helix and ϳ17% ␤-sheet) (Table 1), had larger discrepancies than for TP (Table 1). Discrepancies of this magnitude are often encountered, and the magnitude of the discrepancies for RT-RH 303-778 were considerably less than we have determined for other proteins we are studying (barley chymotrypsin inhibitor 1, hepatitis B virus core protein, human superoxide dismutase 1, and the EAR domain of human ␥2-adaptin [data not shown]) (56,(67)(68)(69). The far-UV CD spectra of apo-TP and apo-RT-RH 303-778 were essentially invariant between pH 5.5 and 9.5, consistent with their structures not varying significantly in this pH range (data not shown).…”
Section: Figmentioning
confidence: 81%